On the structure of eye diseases in children leading to blindness or low vision in various countries of the world - L. S. Khamraeva; D. U. Narzullaeva (Российский офтальмологический журнал)
The review presents differences in the nosological structure of ophthalmic pathology leading to childhood blindness and low vision in different countries. Worldwide, 1.4 million children are blind, about three quarters of whom live in the poorest regions of Africa or Asia. In lowincome countries, the congenital cataract is one of the leading causes of visual impairment in children, while retinopathy of prematurity is more common in middle-income countries. Uncorrected refractive errors both in children and adults, remain a major cause of visual impairment in all countries. The development of new technologies and quality medical care impacts the structure of blindness and low vision causes, as well as their geographical specificities. The analysis showed that much effort is required from large-scale state programs of prevention, early diagnosis, treatment and rehabilitation of children with socially significant eye diseases.